2018
DOI: 10.1017/s0021859617000946
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen application and supplemental irrigation on canopy temperature and photosynthetic characteristics in winter wheat

Abstract: Nitrogen (N) application and irrigation to winter wheat may decrease leaf temperature and enhance photosynthesis: as a result, more photosynthates will be allocated to the grains, resulting in higher grain yields. To investigate this hypothesis, a 2-year field study was conducted with three levels of N fertilizer application (no fertilizer, N0; 240 kg N/ha, N1; 360 kg N/ha, N2) and two different water regimes (rainfed with no irrigation, R; irrigation at the over-wintering, stem elongation and grain filling st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Fois et al (2009) isolated the role of this second mechanism by detecting even after irrigation T c differences using IRTs that viewed canopies only and by detecting leaf conductance differences using a viscous flow porometer. With decreasing N level, Yang et al (2018) found increasing leaf temperature using a handheld thermal camera and found decreasing stomatal conductance using a portable infrared gas analyzer. The third mechanism is that lower N levels can shrink the rooting volume (Nielsen and Halvorson, 1991).…”
Section: Canopy Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…Fois et al (2009) isolated the role of this second mechanism by detecting even after irrigation T c differences using IRTs that viewed canopies only and by detecting leaf conductance differences using a viscous flow porometer. With decreasing N level, Yang et al (2018) found increasing leaf temperature using a handheld thermal camera and found decreasing stomatal conductance using a portable infrared gas analyzer. The third mechanism is that lower N levels can shrink the rooting volume (Nielsen and Halvorson, 1991).…”
Section: Canopy Temperaturementioning
confidence: 99%
“…In contrast, the first mechanism may be less relevant in 2017 because any lag in canopy development due to milder N stress was largely caught up by the beginning of the reproductive period. The second mechanism is that lower N levels can reduce stomatal conductance (Peñuelas et al 1996;Shangguan et al 2000;Fois et al 2009;Yang et al 2018) and modify other leaf properties and/or behaviors (Saneoka et al 2004). Fois et al (2009) isolated the role of this second mechanism by detecting even after irrigation T c differences using IRTs that viewed canopies only and by detecting leaf conductance differences using a viscous flow porometer.…”
Section: Canopy Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In arid areas, the effect of irrigation and fertilization on crop's photosynthesis is very obvious [41][42][43][44] . The increase in irrigation and fertilization will promote the photosynthesis and transpiration of crops [45,46] . However, once a threshold value is exceeded, excessive fertilization and irrigation will inhibit the photosynthetic characteristics of crops [47] .…”
Section: Table 4 Effects Of Different Irrigation and Nitrogen Levels On Nitrogen Transportation In Leaves And Stems And Nitrogen Incremenmentioning
confidence: 99%
“…Low-N stress significantly decreased Chl content and rapid light-response curves of Fm', Fs, qN, Fv/Fm, Fv/F0, and actual photochemical efficiency of PSII of leaves in maize (Wu et al 2019). N fertilizer application significantly increased electron donor and acceptor performance of the PSII reaction center in winter wheat (Yang et al 2018). Our results showed that LNC in sugar beet and the corresponding ChlF parameters varied significantly at different N levels, providing a rich source of information and a theoretical basis for estimating plant nitrogen status using the ChlF technique.…”
mentioning
confidence: 95%